2006
DOI: 10.1002/rcs.89
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided microneurosurgical management of vascular lesions using navigated computed tomography angiography. an advanced IGS technology application

Abstract: This fascinating technique can give some invaluable advantages on the management of cerebral vascular lesions and provides excellent information not always available on traditional digital subtraction angiography investigation. It has also proved to be very accurate, particularly regarding the correlation between the 3D volume-rendered CT angiography and the intraoperative findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Many authors have discussed the advantages of neuronavigation to the surgery of intracranial aneurysms with regard to easier localization of the aneurysm, a better understanding of the vascular anatomy and the hidden structures, help provided to clinoidectomy during premature rupture [9,10,16,17,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have discussed the advantages of neuronavigation to the surgery of intracranial aneurysms with regard to easier localization of the aneurysm, a better understanding of the vascular anatomy and the hidden structures, help provided to clinoidectomy during premature rupture [9,10,16,17,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Brain-aneurysm surgery is based rigorously on anatomical knowledge and preoperative neuroradiological examinations are indispensable in order to understand the spatial arrangement of neck and dome: hence, we do not need navigation to find the aneurysm except in very peculiar cases, such as distal MCA or DACA aneurysms, when navigation can provide effective help [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The current IGS technique was widely used in neurosurgery [9,10] . Robert et al [11] applied AR technique into orthognathic surgery, and compared with the bone translation distance before and after surgery, indicated that AR could prove the accuracy of maxillary 2.5.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have applied this technique to IA surgery using 3D-CTA data [39][40][41][42]. The datasets obtained were loaded onto the neuronavigation system (Medtronic StealthStation Õ or Brainlab VectorVision Õ ) to construct 3D volume-rendered models of the vessels using dedicated 3D software implemented on the workstation.…”
Section: Neuronavigation-guided Aneurysm Clippingmentioning
confidence: 99%